THE IRAN NUCLEAR AGREEMENT AS A REFLECTION OF DISAGREEMENTS IN THE TRANSATLANTIC RELATIONS DURING THE ADMINISTRATION OF THE AMERICAN PRESIDENT DONALD TRUMP - Milutinović, Petar (Political Review, 2023)
At the center of this work is the analysis of the consequences of implementing the Joint Comprehensive Plan of Action (also known as – the Iran nuclear deal) on divergent foreign policy approaches as the main indicators of the mismatch in relations between the United States and the European Union during the administration of the 45th US President Donald Trump. While the US unilaterally withdrew from this agreement, EU member states remained in it. The United States and the European Union, on the one hand, and Iran, on the other, had completely different definitions of their own national security, insisting on their unilateral security, while failing to redefine the problem in the direction of mutual security. However, in addition, the US and EU member states, although both concerned about their own security due to the possible emergence of a nuclear-armed Iran, instead of a complementary approach to the issue had a mutually competing one. Using the case study method, as well as the analytical-deductive method and the content analysis method, the author explains the difference in this approach through the concept of the strategic culture of the US and the EU and concludes that they are a consequence of the different understanding of international relations, but also due to the different identity characters of these two actors. The main thesis of the paper is that the US administration of Donald Trump, with its more realistic and Hobbesian view of international relations, and a different understanding of the US national interest in the Middle East, adopted a different approach to curbing Iran’s nuclear armament ambitions compared to the approach of the European Union, which is conditioned by a more liberal and Kantian nature of its view on international relations. With unilateral foreign policy actions, Trump’s administration risked causing damage and shaking its own credibility in relations with the European Union. On the other hand, the European Union remains committed to multilateralism and the preservation of the Iran nuclear deal. The subject of this research is the direction of the foreign policy actions of the United States and the European Union, in the period from the unilateral withdrawal of Trump’s cabinet from the Iran nuclear agreement on May 8th, 2018, until the assassination of Qasem Soleimani, a general of the Iranian Revolutionary Guard on January 3rd, 2020 in the Republic of Iraq. The current state and perspective of contemporary transatlantic political relations in the context of unilateral withdrawal will be taken into consideration. In accordance with its new foreign policy agenda and strategy, and more inclined to a realistic view of international relations, the Trump administration risked deeper conflicts and divergence with the European Union over regional security issues. Thus, there was a threat to limit the further deepening and strengthening of the transatlantic partnership with the leading member states of the European Union, especially with the government of the Federal Republic of Germany and the government of the Republic of France. Additionally, the subject of research will be the patterns of behavior, embodied in speeches and foreign policy actions, which are consistent with the different approaches of the US and the EU to the problem of preventing the theocratic regime in Iran from developing its nuclear program. Accordingly, the focus will be on the period of the Trump administration, which, with its political will to break off with the legacy of the Obama administration, began to perceive Iran as a factor causing instability in the Middle East region. The Trump administration did not ratify the Iran nuclear agreement and continued to act under its obligations, solely because of the unfavorable benefits and a large number of shortcomings for the US. Thus, the paper will analyze whether the US administration of Donald Trump had a concrete foreign policy strategy in relations with the European Union and Iran. Also, the paper will try to answer the question of whether a unilateral or multilateral approach to regional security problems is more fruitful, taking into consideration the question of whether the unilateral approach of the only superpower in the world is more effective or, on the other hand, an international coalition of states is needed to suppress the Tehran’s nuclear ambitions